Analysis of C-reactive protein/albumin ratio as a predictor of mortality in sepsis patients - Uswatun Hasanah; Irda Handayani; Asvin Nurulita (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Sepsis is a leading cause of death among critically ill patients with infections. Abnormal levels of C-reactive protein (CRP) and albumin in sepsis patients have been shown to predict mortality. Combining the two markers can increase the predictive value of mortality.Objective: The aim of this retrospective cohort study was to determine the cut-off value for the CRP/albumin ratio that could be used to predict mortality in patients with sepsis. Methods: Secondary data from 63 medical records of sepsis patients treated in the ICU of RSUP dr. Wahidin Sudirohusodo Makassar from January 2018 to December 2020 was used. Statistical analysis was performed using the Kolmogorov-Smirnov and Mann-Whitney tests. The prognostic value of the CRP/albumin ratio was analyzed using the ROC curve to obtain a cut-off value. A p-value < 0.05 was considered significant. Results: The sample included 43 deceased and 20 living patients with sepsis. The CRP/albumin ratio was significantly higher in the deceased patients (15.4) than in the living patients (2.4) (p<0.001). The ROC curve analysis revealed a CRP/albumin cut-off value of 4.3 with a sensitivity of 81.4%, specificity of 75.0%, positive predictive value (PPV) of 87.5%, negative predictive value (NPV) of 65.2%, and an accuracy of 79.4%. Conclusion: The study suggests a significant relationship between the CRP/albumin ratio and mortality in patients with sepsis. A CRP/albumin ratio of 4.3 can be used as a predictor of mortality in sepsis patients.